New approaches for the treatment of chagas disease - Pandey, RP; Nascimento, MS; Moore, CE; Raj, VS; Kalil, J; Cunha-Neto, E (Bentham Science Publishers, 2020)
Chagas disease, caused by the protozoan Trypanosoma cruzi is a neglected tropical disease with high prevalence (5.7 million in Latin America, WHO 2015), significant burden, and significant morbimortality mostly due to severe heart disorders during the chronic phase of infection. Chagas disease is endemic in Latin America, and medical care for the disease is the major expense for Brazil's Universal Healthcare System (Sistema Único de Saúde (SUS). The efficacy of the available drugs benznidazole and nifurtimox are low for the chronic phase of Chagas disease, the phase in which most patients are diagnosed, and there are frequent side effects, and drug resistance occurs. The rapid deployment of new drug regimens that are effective for the chronic phase treatment is low-cost and less toxic than the currently available therapy, which is a global priority. Repurposing drugs already in clinical use with other combinations would be the fastest and safest strategy for treating Chagas disease patients. We hypothesize that the combined treatment using repurposing drugs with benznidazole will be more efficacious than benznidazole alone. This needs to be tested further both in vitro and in animal models to understand the efficacy of the treatment before performing human clinical trials. We further hypothesize that producing nanoparticle formulation of the drugs can reduce their toxicity and improve therapeutic use.